2005
DOI: 10.1590/s0100-29452005000300034
|View full text |Cite
|
Sign up to set email alerts
|

Otimização de protocolos para regeneração de plantas in vitro de tangerina 'Cleópatra' (Citrus reshni Hort. ex Tan.)

Abstract: O sucesso de técnicas biotecnológicas no melhoramento in vitro de citros está condicionado à existência prévia de uma metodologia eficiente de regeneração de plantas. O objetivo deste trabalho foi estabelecer um sistema para regeneração de plantas in vitro, via organogênese de tangerina Cleópatra (Citrus reshni Hort. Ex Tan.). Experimentos avaliando concentrações de BAP (benzilaminopurina) e condições de cultivo, posição e polaridade do segmento de epicótilo, no meio de cultura, foram desenvolvidos para maximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
0
8
0
9
Order By: Relevance
“…On the other hand, epicotyl segments are the recommended explant type for obtaining such a positive response to BAP, as expressed by the percentage of responsive explants. Other research works have shown the importance of BAP supplementation in the culture media, as this cytokinin assures a greater number of adventitious buds in in vitro cultivated citrus explants (MoreiraDias et al, 2001;Almeida et al, 2002;Silva et al, 2005aSilva et al, , 2005bSchinor et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, epicotyl segments are the recommended explant type for obtaining such a positive response to BAP, as expressed by the percentage of responsive explants. Other research works have shown the importance of BAP supplementation in the culture media, as this cytokinin assures a greater number of adventitious buds in in vitro cultivated citrus explants (MoreiraDias et al, 2001;Almeida et al, 2002;Silva et al, 2005aSilva et al, , 2005bSchinor et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the development of tissue culture protocols is important for developing transgenic sour orange plants tolerant to CTV. In vitro organogenesis has been obtained in several citrus cultivars by the cultivation of epicotyl and internodal segments in BAP supplemented culture medium (Ghorbel et al, 1998;Moura et al, 2001;Silva et al, 2005aSilva et al, , 2005bSchinor et al, 2006) or with BAP and NAA supplementation (Pérez-Molphe-Balch & Ochoa- Alejo, 1997Moreira-Dias et al, 2000Schinor, 2006). However, very little and inconsistent studies have been carried out specifi cally for sour orange.…”
Section: In Vitro Induction and Regeneration Of Adventitious Buds Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, em levantamentos realizados pela FUNDECITRUS no estado de São Paulo, responsável por cerca de 80% da produção nacional, mostra que tem diminuído a utilização do porta-enxerto limão cravo, chegando a 61% de em 2009 (AMARO;BAPTISTELLA, 2008;NEVES et al, 2012). Este fato pode estar relacionado com o surgimento de novas doenças em laranjeiras enxertadas em limoeiro cravo determinando a diversificação de porta-enxertos, destacando-se a tangerineira "Cleópatra" que apresenta compatibilidade com diversas laranjeiras e não apresenta sintomas de declínio nem morte súbita dos citros (DONADIO et al 1993;ARAUJO;SALIBE, 2002;BALDASSARI et al, 2003;SILVA et al., 2005;GIRARDI, 2005).…”
Section: Introductionunclassified
“…A cultura de tecidos é uma técnica baseada na totipotência celular, que consiste na capacidade da célula vegetal de desenvolver uma planta inteira, desde que submetida a condições que estimulem sua divisão e diferenciação (TORRES; CALDAS; BUSO, 1999 MOURA et al, 2001;COSTA et al, 2004;SILVA et al, 2005aSILVA et al, , 2005bSCHINOR et al, 2006;GARCÍA-LUIS et al, 2006) e segmentos internodal coletados de plantas jovens cultivadas em casa-de-vegetação (MOURA et al, 2001). Porém também existem relatos de obtenção de gemas adventícias a partir de segmento de raiz (BURGER; HACKETT,…”
Section: Cultura De Tecidos Em Citrosunclassified